(untitled) (Academic Journal of Internal Affairs, 2022)
Aim: I am dealing with the tragedy involving 71 deaths, referred to by the press as the ‚death van’ case. The case received a lot of media coverage, with numerous articles in the Hungarian and foreign press. I present the investigative actions taken by the police, the results of the prosecution and the international cooperation through a thesis prepared by a colleague from the KR NNI (National Investigation Bureau of the Rapid Response and Special Police Service). Methodology: The study is descriptive theoretical research. Findings: The study reveals an interesting criminal case which highlights once again the issue of organised crime, the unscrupulous and inhumane treatment of people smuggling groups, who gain millions in profit, almost waging war on the non-profit police forces serving at the border, with no regard for human dignity and the right to life. Value: The processing of the case may also be of interest to the wider public, but readers, researchers and students can also benefit from it.